Importance of the Total Quality in the Social Institutions - Alqriny, Sharefa Saad; Albishi, Amani Ali (Journal of Humanities & Social Sciences, 2023)
This research aims at the importance of the total quality in social institutions. It is about an overview of the concept of quality and total quality and definition of the total quality management, its goals, principles and philosophies and methods of measurement towards the significance of quality in the social institutions, and consideration of the quality application stages in the social institutions and its indicators and the basic requirements of the total quality management system and the areas of its application in various social institutions. Finally, this research recommends adopting unified standards of the total quality in the social institutions taking into account the internal and external users. Securing professional experts to train personnel on applying comprehensive quality and expressed comprehensive appraisal system should be applied to evaluate the performance and the level of service provided and conduct specific studies to determine the strengths and weaknesses.
Keywords: The quality; Total quality; social institutions